(untitled) (Herald of Journalism, 2018)
This article is about history of development Kazakh television. There are an anniversary of TV Kazakhstan-60 years. There is a big way from the first TV program 8 March 1958 year to present time, which mark important broadcasting achievements. From beginning regular broadcasting to creating systems of republic and local TV, mass communication in 1960 years/ This is appearance video broadcasting tape, electronic montage, color image. In 1990 years this is period of commercial television in the independent country. The beginning of XX1 century is the time of new programs and new forms of broadcasting: cable-satellite, digital, interactive, Internet-broadcasting. The aim of article is to show the way of development of TV in Kazakhstan in different periods of country on the background active introduction information-communication technologies and new tendencies of broadcasting in the country in period of globalization and convergence information space. At present time the TV of Kazakhstan is coming to realization industry-innovation development of Kazakhstan, the modernization public acknowledgement, social-cultural development of Kazakh society. Key words: Kazakh television. History of development, information technologies, TV programs, TV channels, broadcasting polic.